Students' perspectives on different teaching methods: comparing innovative and traditional courses in a technology program - Debs, Luciana; Miller, Kurtis D.; Ashby, Iryna; Exter, Marisa (Research in science & technological education, 2019)
Background: A growing number of educators have started exploring student-centered approaches to improve students' learning and satisfaction with courses and programs. While prior research shows a positive impact of such strategies on student learning, further exploration of the perceptions of traditional, lecture-based and other more inquiry-based active learning as experienced by students within the same university is needed. Purpose: To compare students' perceptions of the learning environment in studio-type courses within an innovative pilot student-centered transdisciplinary learning experience to the environment in traditional lecture or lecture-and-lab courses. Program description: An innovative learning experience that employs student-centered teaching strategies to engage students in the transdisciplinary exploration of technology and liberal arts within a technology-focused college in a large land-grant university. Sample: At the end of the first semester, eight students who chose to leave the program were interviewed. At the end of the second semester, eight students who chose to remain in the program and four students who left after the first semester were interviewed. Design/Method: Student were interviewed individually during the end of either their Fall 2014 semester or Spring 2015 semester. A thematic analysis was conducted. Frequency of occurrence was counted and compared for each theme. Results: The most frequently mentioned differences between traditional courses and this learning experience regarded instruction, assessment, and uncertainty. Students enjoyed the flexibility of a more student-centered approach, but struggled with understanding assessment and time management within self-directed transdisciplinary coursework. Student learning preferences appeared to influence their perceptions of each teaching method. Conclusions: Although results seemed to be influenced by personal preferences, time management and dealing with uncertainty were sources of frustration across both groups of students. Scaffolding students in these two areas may help students make an easier transition toward more student-centered learning environments.